2010
DOI: 10.1007/s00455-010-9308-y
|View full text |Cite
|
Sign up to set email alerts
|

Peak Morphology and Scalp Topography of the Pharyngeal Sensory-Evoked Potential

Abstract: The initiation of the pharyngeal stage of swallowing is dependent upon sensory input to the brainstem and cortex. The event-related evoked potential provides a measure of neuronal electrical activity as it relates to a specific stimulus. Air-puff stimulation to the posterior pharyngeal wall produces a sensory evoked potential (PSEP) waveform. The goal of this study was to characterize the scalp topography and morphology for the component peaks of the PSEP waveform. Twenty-five healthy men and women served as r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The aim of this study was to examine the effect of PD on pharyngeal somato-sensation using the PSEP protocol (Wheeler-Hegland et al, 2010, 2011). P1, N1, P2 component peaks were identified in all study participants, while N2 peaks were present in 85% (17/20) of the total participants.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The aim of this study was to examine the effect of PD on pharyngeal somato-sensation using the PSEP protocol (Wheeler-Hegland et al, 2010, 2011). P1, N1, P2 component peaks were identified in all study participants, while N2 peaks were present in 85% (17/20) of the total participants.…”
Section: Discussionmentioning
confidence: 99%
“…The oropharyngeal air-puff elicited various sensations including urge to swallow, cough and gag. In fact, Wheeler-Hegland, et al (2011) examined urge-to-cough, in response to the same pharyngeal air-puff stimulation in young adults, and found that 68% of air-puff trials elicited an urge-to-cough response. Thus, due to the placement of the scope and the sensations reported, it is unlikely that the participants were able to ignore the stimulus throughout the experiment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations